Penerapan Data Mining Dalam Penentuan Proritas Pemesanan Produk Berdasarkan dengan Data Penjualan Barang Menggunakan Algoritma Apriori - Agung Triayudi; Agus Iskandar (Journal of Computer System and Informatics (JoSYC), 2022)
Products cannot be separated from the buying and selling process carried out by customers and sellers. Products that are a priority are, of course, products that are favored by consumers or customers. However, companies often make mistakes in the process of determining which products to order for sale. Errors in the process of determining product orders can result in losses for the company. Therefore, it is necessary to handle this problem properly and appropriately. Therefore, the settlement that should be done should be done by processing the data on the sale of these goods. Data mining is a method that can be used for data processing. But the data processing process carried out in data mining is not done independently. The a priori algorithm is one of the algorithms found in the data mining association technique. The a priori algorithm is widely used to carry out the analysis process on sales data to find sales patterns in the company. The results of the study were 3 items that became the priority of ordering, namely ordinary pants, shorts and t-shirts. With a combination of item sets, if you buy ordinary pants, you also buy shorts with a support value of 10% and a confidence value of 20%. Other item combinations that you get: If you buy regular pants, you also buy T-shirts with a support value of 30% and a confidence value of 60% and the last combination of set items. If you buy shorts, you also buy T-shirts with a support value of 30% and a confidence value of 60%.